ATMOSPHERIC POLLUTION IS A CAUSE OF SERIOUS DISEASES IN HUMAN - Yusupov Mansurjon Mamajonovich; Abduvaliyeva Feruzaxon To‘lqinjonovna (Web of Journals Publishing, 2025)
Air pollution can be defined as an alteration of air quality that can be characterized by measurements of chemical, biological or physical pollutants in the air. Therefore, air pollution means the undesirable presence of impurities or the abnormal rise in the proportion of some constituents of the atmosphere. It can be classified in 2 sections: visible and invisibleair pollution.
Keywords: Chemical, biological, pollution, atmosphere, carbon, nitrogen oxides, nature.